Model Ideal Penerapan Kebijakan Kompensasi dan Ganti Kerugian terhadap Masyarakat yang Terdampak Proyek Strategis Nasional dalam Pembangunan Berkelanjutan - Erlangga, Fahri; Rahman, Faiz Aulia; Wahyudi, Slamet Tri (Wajah Hukum, 2026)
Infrastructure development is currently being increasingly implemented by the Government of the Republic of Indonesia, and a Presidential Regulation of the Republic of Indonesia has been issued concerning the National Medium-Term Development Plan for 2025-2029 which regulates the National Strategic Projects (PSN), as the basis for infrastructure development included in the PSN from 2025-2029. The stages in the PSN are, Land Acquisition for Development in the Public Interest, where these stages must pay attention to fair compensation to affected landowners with the aim of supporting sustainable development and improving the quality of life of the community. The purpose of this study is to determine the application of compensation and compensation policies to communities affected by PSN and the ideal model for implementing compensation and compensation policies to communities affected by PSN in sustainable development. The methods used include the statute approach and the conceptual approach. The results of this study are that the ideal compensation model must be based on a Human Rights-based approach that emphasizes four pillars: justice (adequate and multi-form compensation value), protection (guarantee of no coercion, no criminalization, and special protection for indigenous peoples and vulnerable groups), participation (active involvement since planning, transparency of assessment data, and equality of bargaining position), and remediation (independent appeal mechanism, execution bond, and revocation of the location if the project is canceled so that the land can be reused).